(untitled) (International Journal of Engineering Sciences & Management Research, 2016)
Despite the fact that the general consumer has a preference for choosing apparels made from natural fibers like cotton and linen, there is a tendency for these fabrics to crease. This in turn affects the appearance of the fabrics and thus the overall satisfaction with the fabric. The objective of this paper is to study the effect of spandex yarns on the physical properties of the resultant blended fabrics. 100% cotton and 100% linen fabrics and various blend ratios of cotton/spandex and linen/spandex were tested for crease recovery, Bending stiffness and air permeability. Results showed that spandex has a significant effect on crease recovery of cotton and linen fabrics as both types of fabrics exhibited improved crease recovery. Moreover, bending stiffness of cotton samples was increased by the introduction of spandex yarns at all bending ratios contrarily to linen samples which showed lower bending stiffness at all spandex ratios. Additionally, air permeability showed the same trend as bending stiffness where cotton/spandex blends showed lower air permeability compared to 100% cotton samples, and linen/spandex blends showed higher air permeability compared to 100% cotton samples.